Pengaruh Price to Book Value, Net Profit Margin, Earning Per Share dan Return On Investment Terhadap Harga Saham : Studi Keuangan pada Bank Umum Swasta Nasional yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023 - Yuniar, Elsa; Dicky Jhoansyah; Resa Nurmala (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Banking is one of the financial sectors that is in great demand by investors to invest their capital. This is because the banking sector is a vital sector in a country so it attracts a lot of investor interest. The share price of National Private Commercial Banks has decreased since the last 3 years. One of the factors that influence the rise and fall of share prices is the company's internal factors, including the level of profits obtained, the level of risk faced, and the company's performance. The aim of this research is to analyze the influence of Price to Book Value (PBV), Net Profit Margin (NPM), Earning per Share (EPS), and Return on Investment (ROI) on Stock Prices. The linear regression analysis method is used to evaluate the relationship between the independent variables (PBV, NPM, EPS, and ROI) and the dependent variable (share price). The method used in this research is associative descriptive with a quantitative approach. The sampling technique used is a saturated sample and data analysis using classical assumption test techniques, correlation coefficient test, determination, simultaneous test, multiple linear regression and partial test. Price to Book Value has a calculated t value of 3,908 > from t table and a significant value of 0.001 < 0.05, which means that there is a positive and significant influence between Price to Book Value on Stock Prices. Net Profit Margin has a calculated t value of -0.565 < from t table and a significant value of 0.576 > 0.05, which means that there is a negative and insignificant influence between Net Profit Margin on Share Prices. Earning Per Share has a calculated t value of 3.761 > from the t table with a significant value of 0.001 < 0.05, which means that there is a positive and significant influence between Earning Per Share on Share Prices. Return On Investment has a calculated t value of -1.283 < from the t table with a significant value of 0.208 > 0.05 which can be interpreted as meaning that there is a negative and insignificant influence between Return On Investment on Share Prices.